Migration and Media in Finland - Croucher, Stephen M. author. aut Link
X, 122 p.
Keywords: This book combines various theoretical approaches to explore how Finland and its people responded to the European Union (EU) refugee crisis. Combining interviews with Finns, voluntary migrants to Finland and refugees in Finland, the text presents differing perspectives on migration in this country. Key themes addressed in the text include the extent to which the different groups perceive one another to be economic, political, and cultural threats to Finnishness. In addition, the cultural fusion of Finnish and migrant culture is presented as a threat and opportunity for Finland and its future.